2013
DOI: 10.1089/bfm.2012.0044
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Promoters of Home-Based Pasteurization of Breastmilk Among HIV-Infected Mothers in Greater Dar es Salaam, Tanzania

Abstract: Background: For the past decade, heat-treating breastmilk has been an infant feeding option recommended by the World Health Organization as a strategy to reduce vertical transmission. However, little is known about field experiences with it. Our primary objective was to explore the barriers and promoters of the implementation of breastmilk pasteurization, ''flash-heating'' (FH), in the real-world setting of Dar es Salaam, Tanzania. Subjects and Methods: Nineteen in-depth interviews were conducted with particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
(16 reference statements)
0
3
0
3
Order By: Relevance
“…Research on home heat treated breastmilk in Tanzania showed that some mothers did not continue the procedure for long as it was considered too much work and it was easier to give alternative fluids [ 13 ]. The same barriers might be encountered in Kilifi when cooking is done on firewood or charcoal and cow’s milk or maize porridge is easily available to the household.…”
Section: Discussionmentioning
confidence: 99%
“…Research on home heat treated breastmilk in Tanzania showed that some mothers did not continue the procedure for long as it was considered too much work and it was easier to give alternative fluids [ 13 ]. The same barriers might be encountered in Kilifi when cooking is done on firewood or charcoal and cow’s milk or maize porridge is easily available to the household.…”
Section: Discussionmentioning
confidence: 99%
“…25 Complementary feeding, recommended to begin at 6 months of age, is expected to take place alongside continued breastfeeding. They may cease breastfeeding earlier than recommended to reduce the risk of HIV transmission 23,30 or because of perceived milk insufficiency, which is often exacerbated by food insecurity. [27][28][29] HIV-infected mothers face unique challenges to feed their infants in accordance with evidence-based recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…Participação em programas de prevenção 13,16,[18][19][20][23][24][25][26][27][28] Acolhimento da equipe de saúde 11,16,21,24 Educação em saúde 20 Conforto das condições de saúde 24 Divulgação do estado sorológico [16][17][18][19] Aderir às medidas de profilaxia da TV 11,[16][17][18][19] Repercussões na saúde sexual 13 Deus e a fé 15,24,27 Divulgação do estado sorológico 29 Motivação para aceitar o diagnóstico e o tratamento 24 repercussões na saúde sexual: consideraram-se com maior capacidade para negociar o planejamento familiar, além do uso de preservativo, e solicitar ao companheiro que realizasse o teste de anticorpos do HIV.…”
Section: Suporte Instrumentalunclassified
“…As organizações comunitárias com patrocínio externo fornecem maior apoio a discussões sobre profilaxia da transmissão HIV do que outros grupos, entretanto a pequena participação masculina pode ser um fator que contribui para baixa adesão dessas medidas. 18 Em outros países, a utilização de algumas estratégias de educação em saúde, 20 desenvolvidas por educadores pares foi destacada. Estes são trabalhadores de saúde que devem ser membros das comunidades, responsáveis pelas atividades de aconselhamento sobre os cuidados de saúde.…”
Section: Suporte Instrumentalunclassified
See 1 more Smart Citation